IMPLEMENTASI INTERNET OF THINGS PADA SISTEM PEMANTAUAN TEKANAN DARAH LANSIA - Pratama, Muhammad Ilham; Irianto, Kurniawan Dwi (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2024)
The expanding elderly population demands special attention, including health monitoring. Blood pressure is an important health indicator for the elderly and should be checked on a regular basis to avoid complications. According to the World Health Organization (WHO), around 1.13 billion people worldwide were diagnosed with hypertension in 2015, which equates to one in every three people. Because of the difficulties in getting to hospitals, the elderly do not constantly monitor their blood pressure. Even while measuring at home, people may neglect to document the results. This paper presents the development of an IoT-based blood pressure monitoring system for the elderly that utilizes the MPX5700AP sensor and can display and store measurements via Blynk and Telegram. Data and information collection, requirement identification, system design, device assembly, implementation, system testing, and assessment are all part of the approach. The test results indicate that the system can precisely detect blood pressure. Thus, this technology can assist the elderly by automatically capturing blood pressure measurements.